Interplay of Digital Media and Democracy: An Analysis of Politics of Twitter Ban in Nigeria (Journal of Management and Social Sciences, 2025)
This paper investigates the positions of state and non-state actors during the ban of Twitter by the Nigerian government between June 4, 2021 and January 13, 2022. It answers questions about whether non-state actors resisted the ban due to Twitter's contributions to democratic, civic space, and economic growth, and whether state actors considered the medium a threat to the country's unity and sovereignty with supportive evidence. Conflict theory and the Advocacy Coalition Framework are used as theoretical and analytical frameworks to explore the different beliefs and interests of the actors involved. The study found that the ban generated a series of reactions from these actors, leading to the development of three forms of narratives from the policy and advocacy coalition beliefs. The study concludes that examining the views of state and non-state actors during the ban period provides insights into the different interests, beliefs, and values that shape policy conflicts.Keywords: Conflict, Democracy, Twitter, Nigeria, Policy Actors